Jijñāsā saṃkalana - Ray, Sibnarayan (Jijñāsā, 2022)
Articles on Bengali literature and culture; selected and compiled from the last twelve years of the Bengali quarterly Jiñjāsā.
Literaturverzeichnis: Seite 337-342
Keywords: Aufsatzsammlung; Bengali literature; 20th century; History and criticism.; West Bengal (India); Civilization.